Bathara Kala : An Interpretation of The Concept of Time in Javanese Culture - Lardianto Budhi; Slamet Subiyantoro; Adam Wahida (Universitas Sebelas Maret, 2022)
This study aims to analyze the concept of time in Javanese culture through the existence of the character Bathara Kala in the wayang kulit play Ruwat Murwakala and its influence on people's attitudes and habits in living daily life. The concept of time affects the cognitive processes in a person and subsequently has an impact on his reasoning. This will then also affect his behavior and character. In contrast to the western perspective, eastern people, including Indonesia, have a different perception of time. Javanese people have their own view of time. This can be seen from social attitudes, spiritual attitudes and attitudes towards what was being faced yesterday, today, and tomorrow. The semiotic perspective was chosen to analyze the data obtained through literature study techniques, interviews, direct observation and documentation. The results of this study shows that the Javanese concept and perception of time reflected through the character of Bathara Kala in ruwatan murwakala has an impact on the behavior and habits of everyday people. The influence is, among others, through a metaphor for time, for example the word